Strategi Membangun Masyarakat Yang Sehat dan Peduli Lingkungan di RT 50 Kelurahan Betungan Kota Bengkulu - Safitri, Lindia; Anjaly, Ana; Ardhika, Bagus Dwiky; Mansur, Irfan; Tentara, Brend; Rozzi, Yoli Andi; Nur’aini, Hesti; Fariadi, Herri (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Healthy exercise and communal work are effective community-based strategies for shaping a healthy and environmentally conscious society. In RT 50, Bengtungan Subdistrict, Bengkulu City, these two activities are carried out routinely and have shown positive impacts in various aspects. Group exercise not only improves residents' physical fitness but also strengthens social interaction. Meanwhile, community clean-up activities encourage environmental awareness, evident through improved cleanliness, waste management, and increased social solidarity. This study aims to illustrate the strategic role of these activities in promoting a healthy and clean lifestyle in the community. The results show that active citizen participation plays a crucial role in the success of the program and can serve as a model for other areas.